2008
DOI: 10.1124/jpet.107.133702
|View full text |Cite
|
Sign up to set email alerts
|

Compounds That Increase or Mimic Cyclic Adenosine Monophosphate Enhance Tristetraprolin Degradation in Lipopolysaccharide-Treated Murine J774 Macrophages

Abstract: Tristetraprolin (TTP) is a trans-acting factor that can regulate mRNA stability by binding to the cis-acting AU-rich element (ARE) in the 3Ј-untranslated region in mRNAs of certain transiently expressed genes. The best-studied target of TTP is tumor necrosis factor (TNF)-␣. By binding to ARE, TTP increases the degradation of TNF-␣ mRNA, thereby reducing the expression of TNF-␣. We examined the effects of cAMP analogs and the cAMP-elevating agents forskolin and ␤ 2 -agonists on lipopolysaccharide (LPS)-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Our results showed that cAMP/PKA pathway was involved in the inhibitory effect of EX‐4 on LPS‐induced iNOS protein expression. These findings suggest that cAMP/PKA pathway is implicated in iNOS protein destabilization, which is supported by others' studies that cAMP enhanced tristetraprolin (TTP) protein degradation in LPS‐treated J774 macrophages without altering TTP mRNA degradation rate [Jalonen et al, 2008] and EX‐4 inhibited IL‐1β‐induced iNOS protein expression via cAMP/PKA system in INS‐1 beta‐cells [Kang et al, 2009], and also EX‐4 reduced high glucose‐induced thioredoxin interacting protein expression via cAMP/PKA signaling in INS‐1 cells [Shao et al, 2010].…”
Section: Discussionsupporting
confidence: 58%
“…Our results showed that cAMP/PKA pathway was involved in the inhibitory effect of EX‐4 on LPS‐induced iNOS protein expression. These findings suggest that cAMP/PKA pathway is implicated in iNOS protein destabilization, which is supported by others' studies that cAMP enhanced tristetraprolin (TTP) protein degradation in LPS‐treated J774 macrophages without altering TTP mRNA degradation rate [Jalonen et al, 2008] and EX‐4 inhibited IL‐1β‐induced iNOS protein expression via cAMP/PKA system in INS‐1 beta‐cells [Kang et al, 2009], and also EX‐4 reduced high glucose‐induced thioredoxin interacting protein expression via cAMP/PKA signaling in INS‐1 cells [Shao et al, 2010].…”
Section: Discussionsupporting
confidence: 58%
“…Although TTP expression in the NZB/W mouse model is currently unknown, studies using cells derived from TTP knockout mice have confirmed TTP is not the sole regulator of inflammatory mediator mRNA stability but have implicated it in the development of autoimmunity [61,62]. TTP knockout mice develop a systemic inflammatory syndrome with severe arthritis and autoimmunity, as well as medullary and extramedullary myeloid hyperplasia [63].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proteasomal inhibitors have become an attractive approach to activate Nrf2-mediated anti-oxidative pathway in the prevention of various oxidative stress-initiated diseases [5]. Among proteasome inhibitors, MG132 is specific, potent, reversible, and cell permeable and plays a key role in blocking the degradation of ubiquitin-conjugated proteins in mammalian cells by the 26S complex without affecting its ATPase or isopeptidase activities [6]. …”
Section: Introductionmentioning
confidence: 99%